Rotation measure and synchrotron emission signatures in simulations of magnetized galactic discs - Rappaz, Yoan; Schober, Jennifer; Girichidis, Philipp (Monthly notices of the Royal Astronomical Society, 2022)
We analyse observational signatures of magnetic fields for simulations of a Milky Way-like disc with supernova-driven interstellar turbulence and self-consistent chemical processes. In particular, we post-process two simulations data sets of the SILCC Project for two initial amplitudes of the magnetic field, B0 = 3 and 6 μG, to study the evolution of Faraday rotation measures (RM) and synchrotron luminosity. For calculating the RM, three different models of the electron density ne are considered. A constant electron density, and two estimations based on the density of ionized species and the fraction of the total gas, respectively. Our results show that the RM profiles are extremely sensitive to the ne models, which assesses the importance of accurate electron distribution observations/estimations for the magnetic fields to be probed using Faraday RMs. As a second observable of the magnetic field, we estimate the synchrotron luminosity in the simulations using a semi-analytical cosmic ray model. We find that the synchrotron luminosity decreases over time, which is connected to the decay of magnetic energy in the simulations. The ratios between the magnetic, the cosmic ray, and the thermal energy density indicate that the assumption of equipartition does not hold for most regions of the ISM. In particular, for the ratio of the cosmic ray to the magnetic field energy the assumption of equipartition could lead to a wrong interpretation of the observed synchrotron emission.
Gesehen am 21.04.2022